Phronesis and Quiddity in Management A School of Knowledge Approach - Kase, Kimio; González-Cantón, César; Nonaka, Ikujiro; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Phronesis and Quiddity in Management addresses the issue of the excellence in judgment-making, its concept and characterisation. This book investigates first into what constitutes excellent managerial skills centred on leadership revolving around judgement-making (rather than decision-making) and second into whether they can be taught.
Keywords: Management; International business enterpris; International economics; Philosophy (General).; Leadership; Innovation/Technology Management; International Business; Management; International Economics; Philosophy, general; Business Strategy/Leadership.